Reisseronia (Reisseronia) hellersi Sobczyk & Werno, sp. n. from Northern Spain (Lepidoptera: Psychidae) - T. Sobczyk; A. Werno (SHILAP, 2021)
A new Psychidae, Reisseronia (Reisseronia) hellersi Sobczyk & Werno, sp. n. is described from Northern Spain. This is the first species of this genus known from the Iberian Peninsula. The differences to Reisseronia (Reisseronia) tarnierella (Bruand, 1850), the species with the largest and most western distribution in Europe, are shown. Above all, the broader scales on the fore wings characterize R. (R.) hellersi compared to R. (R.) tarnierella. In addition, an overview of European Reisseronia species is given.